2016
DOI: 10.1016/j.ajhg.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Variants in HNRNPH2 on the X Chromosome Are Associated with a Neurodevelopmental Disorder in Females

Abstract: Via whole-exome sequencing, we identified six females from independent families with a common neurodevelopmental phenotype including developmental delay, intellectual disability, autism, hypotonia, and seizures, all with de novo predicted deleterious variants in the nuclear localization signal of Heterogeneous Nuclear Ribonucleoprotein H2, encoded by HNRNPH2, a gene located on the X chromosome. Many of the females also have seizures, psychiatric co-morbidities, and orthopedic, gastrointestinal, and growth prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 27 publications
7
86
1
Order By: Relevance
“…Of note, she exhibited progressive deterioration in adulthood, particularly affecting her motor skills with regression in her ability to walk, and increasing movement disorder consisting of tremors and dystonia. This regression would support the hypothesis of a neurodegenerative pathogenesis of the disease caused by the accumulation of dysfunctional proteins in the cytoplasm as suggested by Bain et al (), also in the long term.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Of note, she exhibited progressive deterioration in adulthood, particularly affecting her motor skills with regression in her ability to walk, and increasing movement disorder consisting of tremors and dystonia. This regression would support the hypothesis of a neurodegenerative pathogenesis of the disease caused by the accumulation of dysfunctional proteins in the cytoplasm as suggested by Bain et al (), also in the long term.…”
Section: Discussionsupporting
confidence: 86%
“…Focused exome sequencing identified the following heterozygous variant in HNRNPH2 [NM_019597.4]: c.617G>T, de novo . The c.617G>T substitution causes amino acid change at codon 206 (p.Arg206Leu), which is located within the glycine‐rich domain containing the nuclear localization sequence (NLS) (Bain et al, ). The variant is absent from the public population databases, was predicted as damaging by all three in silico prediction tools, and had a PHRED score of 24.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a novel missense mutation in the NLS of hnRNPA1, which causes redistribution of hnRNPA1 from the nucleus to the cytoplasm, was identified as a cause of familial ALS (Liu et al, 2016), expanding the repertoire of NLS mutations in ALS-associated proteins. Interestingly, mutations that disrupt the NLS in a related protein, hnRNPH2, cause neurodevelopmental delay and autism (Bain et al, 2016). …”
Section: Circumstantial Evidence For a Nucleocytoplasmic Transport Dementioning
confidence: 99%
“…Pilch et al recently reported that mutations in HNRNPH1 may cause Bain type syndromic mental retardation (MRXSB) in boys . So far, this syndrome has been only described in females caused by de novo mutations in the X‐linked HNRNPH2 gene . It was thought that the disease is embryonic lethal in hemizygous males.…”
mentioning
confidence: 99%